Evaluation of metastatic potential of prostate cancer - Yoshitomo Chihara; Hiroki Kuniyasu; Kiyohide Fujimoto; Yoshihiko Hirao (Frontiers Media S.A., 2011)
We aimed to establish a method for evaluating malignant potential of prostate cancer using prostatic core needle biopsy (PCNB) before prostatectomy. If we can know the final pathological stage before treatment, we can select the most suitable therapeutic tactics. We then examined the expression of E-cadherin and type IV collagenase (MMP-9/-2), which play essential role in cancer cell invasion and metastasis. The expression ratio of MMP-9/-2 to E-cadherin (MER) is revealed as the relevant marker correlated with the final pathological stage and Gleason score by prostatectomy specimens. We next confirmed the significance of MER in PCNB, which means PCNB MER enables the prediction of the final pathologic stage at the cancer diagnosis. However, the methodology measuring MER is complicated to produce an observer-to-observer deviation. We then establish a bicolor fluorescent ISH (bicolor FISH) with a computerized fluorescence detector- based system. By this method, we can reduce an observer-to-observer deviation and a slide-to-slide deviation. The bicolor FISH-based MER is a useful tool for the preoperative evaluation of the final pathologic stage, by which we can assure a decision of prostatectomy indication.